Esther and Her Royal Predecessors - Oxsen, Kate (Trinity College Dublin, School of Religion, Loyola Institute, 2021)
Previous scholarly conversations regarding royal women in the Hebrew Bible (HB) focus solely on the women in the Deuteronomistic History (DH). Yet Queen Esther, one of the fullest portrayals of a royal woman in the HB, is intentionally left out of these discussions. However, when one looks closely at the narrative of Esther, there are several obvious links to the DH, primarily Saul (2 Samuel 15) but also to the text of 1 Kings 1. There are also more subtle connections between the Book of Esther and these royal narratives in the DH, such as its focus on monarchy and the active presence of royal women. In light of these connections, this project demonstrates the ways in which bringing Esther into the conversation about royal women can enrich the discussion of queens in biblical literature by way of narrative analysis. It looks at Esther in light her most prominent royal predecessors in the HB: Abigail, Bathsheba, Jezebel, and Athaliah. Esther serves as the locus of this project, but Abigail, Bathsheba, Jezebel, and Athaliah are also seen with fresh eyes, as reading them alongside Esther inevitably encourages one to reflect upon their characters and narratives, as well. This project contributes new insights into the expectations and roles of royal wives, as presented by biblical writers
Keywords: Old Testament; Hebrew Bible; Queenship; Royal Women; Esther; Abigail; Bathsheba; Jezebel; Athaliah